Brief narrative practice in single-session therapy - Cooper, Scot J. (New York, NY : Routledge, 2024)
"Brief Narrative Practice in Single-Session Therapy emphasizes collaboration, meaning making, and relational ethics in single-session conversations. Chapters provide a thorough orientation to the therapy and address the diverse circumstances clinicians face in these conversations. Separating from many long-held traditions in therapy, this book explores a guiding framework and the accompanying micro-skills that therapeutic conversations demand. In these pages, readers will learn how to recalibrate their listening habits and talk differently about problems in ways that help them quickly hear and generate possibilities. All those who provide psychotherapy, counselling, and coaching in time-constrained contexts will find this book useful and engaging, including those working in crisis and call-in settings, walk-in clinics, medical centres, and live-in contexts where change conversations are brief"--
Keywords: Single-session psychotherapy; Narrative therapy; Single-session psychotherapy -- Methodology; Narrative therapy -- Methodology; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Mental Health